(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Potts disease, also known as tubercular spondylitis, is a well known condition in developing countries. Here we report a case of Potts disease with bilateral psoas abscesses in a 51 years diabetic male with poor glycaemic control. Diagnosis is done on the basis of history, physical examination, plain radiology & MRI imaging and history of exposure to a tuberculosis case. He was treated conservatively and responded well to anti-tubercular chemotherapy. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21073